Rectangular phase sound sources focusing radiated energy of vibrations - PUCH, Andrzej (Archives of Acoustics, 1987)
This paper is concerned with the acoustic field in the Fresnel zone of a focusing rectangular phase sound source with the following amplitude distributions of the vibration velocity: uniform, HAMMING'S, HANNING'S and BLACKMAN'S. Amplitude distributions of the acoustic potential were determined along the main axis of such a sound source and in planes parallel to the main axis. It was found that in the case of HAMMING'S, HANNING'S and BLACKMAN'S amplitude distributions of the vibration velocity, the amplitude distribution of the acoustic potential along the amin axis has only one maximum, which is situated near the focal point. This maximum has the highest value for HAMMING'S distribution. When the dimensions of the source are increased, the value of the maximum increases and it is shifted towards the focal point, while its width decreases. Amplitude distributions of the acoustic potential in planes parallel to the axis of the source have relatively narrow maxima, which occur along this axis. They are narrower than for a Gaussian amplitude distribution of the vibration velocity, which was analysed in previous papers. Besides the main maximum also side maxima occur in the focal plane. They are strongly damped for HAMMING'S, HANNING'S and BLACKMAN'S distributions.Therefore, the acoustic field of a focusing rectangular phase sound source with HAMMING'S, BANNING'S and BLACKMAN'S distributions is relatively uniform in the Fresnel zone.